Distress tolerance and emotional regulation in individuals with alcohol use disorder - Zaorska, Justyna; Rydzewska, Małgorzata; Kopera, Maciej; Wiśniewski, Paweł; Trucco, Elisa M.; Kobyliński, Paweł; Jakubczyk, Andrzej (Frontiers in Psychiatry, 2023)
Background Previous research suggests that low distress tolerance may be associated with poor emotion regulation, contribute to drinking to cope motives, and predict alcohol-related problems in non-clinical populations. However, little is known about the ability to tolerate distress among individuals with alcohol use disorder (AUD) and its association with emotional dysregulation. The aim of this study was to examine the link between emotional dysregulation and a behavioral measure of distress tolerance among individuals with AUD. Methods The sample consisted of 227 individuals with AUD enrolled in an 8-week abstinence-based inpatient treatment program. Behavioral distress tolerance was assessed using a test of ischemic pain tolerance and the Difficulties in Emotion Regulation Scale (DERS) was used to assess emotion dysregulation. Results Distress tolerance was significantly associated with emotional dysregulation even when accounting for alexithymia, depressive symptomatology, age, and biological sex. Conclusion The current study provides preliminary support for an association between low distress tolerance and emotion dysregulation in a clinical group of patients with AUD.